2020
DOI: 10.1111/plb.13159
|View full text |Cite
|
Sign up to set email alerts
|

Breeding systems of floral colour forms in theDrosera cistifloraspecies complex

Abstract: Variation in plant breeding systems has implications for pollinator‐mediated selection on floral traits and the ecology of populations. Here we evaluate pollinator contribution to seed production, self‐compatibility and pollen limitation in different floral colour forms of Drosera cistiflora sensu lato (Droseraceae). These insectivorous perennial plants are endemic to fynbos and renosterveld vegetation in the Cape Floristic Region of South Africa, and the species complex includes five floral colour forms (pink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Similarly, Johnson et al found that patterns of color variation in Drosera cistiflora, a species pollinated by beetles, are associated with different pollinator communities. Given that these beetle species discriminate among color forms (von Witt et al, 2020), the authors conclude that beetle pollinators are a significant factor in the evolution of D. cistiflora flower color. This is one of the first reports of flower color selection by beetles (see Streinzer et al, 2019).…”
Section: Flower Color Variation At the Microevolutionary Scalementioning
confidence: 99%
“…Similarly, Johnson et al found that patterns of color variation in Drosera cistiflora, a species pollinated by beetles, are associated with different pollinator communities. Given that these beetle species discriminate among color forms (von Witt et al, 2020), the authors conclude that beetle pollinators are a significant factor in the evolution of D. cistiflora flower color. This is one of the first reports of flower color selection by beetles (see Streinzer et al, 2019).…”
Section: Flower Color Variation At the Microevolutionary Scalementioning
confidence: 99%
“…First, the flower pigmentation of numerous species exhibits considerable intraspecific variation [reviewed by Sapir et al (2021)]. Intraspecific flower color variation can be discrete (Schemske and Bierzychudek, 2007;Streinzer et al, 2019;von Witt et al, 2020;Buide et al, 2021) or continuous, e.g., covering the spectrum of white, pink and purple in Trifolium pratense (Figure 1), orchids (Sletvold et al, 2016;Dormont et al, 2019) and the Iris atropurpurea complex (Roguz et al, 2020). The amount of pigment that is synthesized is a quantitative trait, and therefore small changes in the pigment synthesis pathway can yield appreciable changes in color (Shrestha et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…250 species known worldwide (Fleischmann et al, 2018). Some Drosera flowers have characteristics that are considered adaptive for entomophily (Witt et al, 2020). Various insect species, including flower flies (El‐Sayed et al, 2016; Murza et al, 2006; Tagawa et al, 2018), bees (Wilson, 1995), and beetles (Anderson, 2010), have been recorded as effective pollinators, facilitating out‐crossing.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, many Drosera are self‐compatible to make seeds by autogamy and do not depend on pollinators for reproduction (Murza & Davis, 2003; Pietropaolo & Pietropaolo, 1986; Sciligo, 2009). Witt et al (2020) suggested that the low pollinator dependence in Drosera is associated with the ephemerality of their habitats. The habitats of many Drosera species are seasonal wetlands, where attracting pollinators constantly would be difficult.…”
Section: Introductionmentioning
confidence: 99%